Teaching of Chemistry Applied. Development of a Laboratory-scale Fire Started - Guntero, Vanina Alejandra (2018)
The present laboratory work based in the preparation of fire started is proposed as an alternative in the teaching of chemistry for students of high school, with the purpose of articulate and integrate the abilities of students from the knowledge acquired. In this sense, is proposed the progression of learning, so that students develop from a specific concept towards the understanding of a phenomenon through a concrete and accessible teaching practice that assure that interaction. This practice allowed consolidating and expanding the teaching-learning process. Based on the interest in the topic propounded, the students were able to internalize the knowledge, reaching a satisfactory theoretical-practical relationship.